Macronutrient-Based Predictive Modelling of Bioconversion Efficiency in Black Soldier Fly Larvae (Hermetia illucens) Through Artificial Substrates - Laurens Broeckx; Lotte Frooninckx; Siebe Berrens; Sarah Goossens; Carmen ter Heide; Ann Wuyts; Mariève Dallaire-Lamontagne; Sabine Van Miert (Insects)
This study explores the optimisation of rearing substrates for black soldier fly larvae (BSFL). First, the ideal dry matter content of substrates was determined, comparing the standard 30% dry matter (DM) with substrates hydrated to their maximum water holding capacity (WHC). Substrates at maximal WHC yielded significantly higher larval survival rates (p = 0.0006). Consequently, the WHC approach was adopted for further experiments. Using these hydrated artificial substrates, fractional factorial designs based on central composite and Box–Behnken designs were employed to assess the impact of macronutrient composition on bioconversion efficiency. The results demonstrated significant main, interaction, and quadratic effects on bioconversion efficiency. Validation with real-life substrates of varied protein content, including indigestible feather meal, affirmed the predictive model’s accuracy after accounting for protein source digestibility. This research underscores the importance of optimal hydration and macronutrient composition in enhancing BSFL growth and bioconversion efficiency.